Hybridized Intrusion Detection and Prevention System Using Static IP Address - Okunade, Oluwasogo Adekunle (Covenant Journal of Informatics and Communication Technology, 2019)
Internet growth and constant increase in traffic volume, resulted into various misuse and attacks on the internet, that increases security challenges over intrusion detection and prevention system against sophisticated attacks. This has become paramount importance since single mode intrusion detection systems have a lot of difficulties in protecting system and network from sophisticated attacks. However, this paper propose hybridized intrusion detection and prevention system using static IP address whereby the incoming packets are examined for attacks at two layers, both at network level as network based intrusion detection and prevention system (NIDPS) and at host level as host based intrusion detection and prevention system (HIDPS) to further strength system and network security. This help to prevent against intrusion, minimize false positive and negative alert and maximize true positive and negative detection. This technique handled sufficient information in a real-time to account for irregular use of networks and computer systems in a real time.